2020
DOI: 10.1186/s13071-020-04297-7
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the immunomodulatory properties of Haemonchus contortus adhesion regulating molecule 1 interacting with goat T cells

Abstract: Background Gastrointestinal nematodes could release excretory-secretory (ES) proteins into the host environment to ensure their survival. These ES proteins act as immunomodulators to suppress or subvert the host immune response via the impairment of immune cell functions, especially in chronic infections. In our preliminary study, Haemonchus contortus adhesion-regulating molecule 1 (HcADRM1) was identified from H. contortus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Hence, anti-rHcADRM1 IgG was employed in the parallel passive trial and was shown to confer encouraging levels of protection to inoculated goats by reducing cumulative FEC and worm burden by 46.7 and 56.2%, respectively. In this study, relatively high levels of mucosal and serum anti-rHcADRM1 IgG were present in HcADRM1 preparations-immunized goats over the time-courses of both trials 1 and 2, which might impede H. contortus larvae development given the crucial roles of HcADRM1 protein in transcriptional regulation and cell growth (Lu et al, 2020c). In most cases, immunization with native antigen preparations appears to induce higher levels of protective immune responses against H. contortus compared to the corresponding recombinant or synthetic forms.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Hence, anti-rHcADRM1 IgG was employed in the parallel passive trial and was shown to confer encouraging levels of protection to inoculated goats by reducing cumulative FEC and worm burden by 46.7 and 56.2%, respectively. In this study, relatively high levels of mucosal and serum anti-rHcADRM1 IgG were present in HcADRM1 preparations-immunized goats over the time-courses of both trials 1 and 2, which might impede H. contortus larvae development given the crucial roles of HcADRM1 protein in transcriptional regulation and cell growth (Lu et al, 2020c). In most cases, immunization with native antigen preparations appears to induce higher levels of protective immune responses against H. contortus compared to the corresponding recombinant or synthetic forms.…”
Section: Discussionmentioning
confidence: 70%
“…2E and F). Given that the preliminary work identified higher HcADRM1 mRNA expression in male worms of H. contortus than in female ones (Lu et al, 2020c), we anticipated the administration of HcADRM1 preparations would show a significant protection pattern against male adults. However, similar to trial 1, no notable changes in either female or male worm burdens (P = 0.051 and P = 0.161, respectively) were observed between groups E and F (Fig.…”
Section: Reductions In Fecal Egg Shedding and Worm Burdensmentioning
confidence: 99%
See 2 more Smart Citations
“…Another ES antigen, adhesion-regulating molecule 1 (HcADRM1), was expressed in E. coli in its soluble form and tested in goats. Results indicated that vaccination with recombinant HcADRM1 induced a slightly protective immunity in comparison to rHcABHD, with reductions of 48.9% in FECs and up to 58.6% in worm burdens [ 68 , 96 ].…”
Section: Vaccination Against H Contortusmentioning
confidence: 99%